Utilization of Household Waste Through Waste Bank and Financial Management - WIDIASTUTI, Retno; AKBAR, Dharmawan Iqbal; MAULA, Farisa Nur; FATIMAH, Annisa; HARIS, Zainal Abdul (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Pulotondo Village is located in Ngunut District, Tulungagung Regency, East Java, with a population of 3,679, most of whom work in the agricultural sector. The problems and issues in this village are the people's habit of throwing household waste carelessly so that it can damage the environment. A dirty and damaged agricultural environment, with substandard irrigation quality, can kill the agricultural sector in the village. This activity aims to train BUMDes to have a significant role in converting household waste into products that have added value for community welfare, primarily through the Waste Bank program and its financial management. The methods used in this study were lectures, discussions and questions and answers with village managers, BUMDes, PKK group and village residents. The results of this training were an increase in the knowledge and skills of village residents in managing waste through the Waste Bank program.